Three‐Phase Segmentation of Solid Oxide Fuel Cell Anode Materials Using Lab Based X‐ray Nano‐Computed Tomography. Issue 1 (2nd February 2017) - Heenan, T. M. M.; Bailey, J. J.; Lu, X.; Robinson, J. B.; Iacoviello, F.; Finegan, D. P.; Brett, D. J. L.; Shearing, P. R.
Abstract: Triple‐phase boundaries are an important microstructural metric to assess the performance and durability of solid oxide fuel cell electrodes and are known to significantly influence the performance at cell level. In recent years many advancements have been made in the quantification of TPBs including the use of focused ion beam scanning electron microscopes and synchrotron X‐ray tomography, although neither technique comes without limitation; the former being destructive and the latter having limited availability. This work demonstrates the first example of the application of lab‐based X‐ray nano‐CT for non‐destructive, microstructural characterization of a SOFC electrode, where three‐phase segmentation has been achieved. A SOFC anode cermet consisting of nickel and yttria‐stabilized zirconia was imaged under X‐ray using two fields of view: 64 µm × 64 µm and 16 µm × 16 µm, with compositional data displayed for several samples at the two resolutions. This work highlights the possibility of three‐phase segmentation using lab‐based equipment allowing non‐destructive quantification and mapping of triple‐phase boundaries without the need for synchrotron radiation.